Education of family values among orphans. - Kozyrev M. V. (Social-Psychological Issues of a Contemporary Family: Value of Motherhood and Childhood, 2021)
Education of family values among orphans. Annotation: This article discusses the problem of spiritual and moral education of orphans in orphanages and boarding schools. This topic is very relevant, since we are talking about children from an early age who have seen a decline in morality - the manifestation of cruelty and violence on the part of parents, family breakdown, alcoholism, drug addiction, vagrancy, which contributes to the loss of the family function of transmitting significant cultural and life values to children, reducing the level of spiritual culture of most pupils.
Keywords: воспитание; нравственность; семья; дети; children; morality; upbringing; семейные ценности; family values; Keywords: family; orphanhood; сиротство